2021
DOI: 10.1088/1755-1315/646/1/012059
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of Hydroxyapatite (HAp) derived from clamshell as active ingredients in sunscreen product

Abstract: Commercially, Avobenzone and Oxybenzone act as absorber of UVA and UVB while titanium dioxide (TiO2) and zinc oxide (ZnO) are the physical “blockers” of UV radiation in sunscreen formulation. These active ingredients are known to cause photo-allergic reactions, while others are suspected as estrogen disrupters. Due to this concern, hydroxyapatite (HAp) is derived from clam shell in order to replace Avobenzone and Oxybenzone as organic component in UV absorber. The HAp has arisen as potential candidates to repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The sunscreen formulated with the combination of conventional UV filter agents and special organic ingredients like octinoxate, octisalate, oxybenzone, homosalate, avobenzone, octocrylene has shown better SPF values 40,42 . While the combination of these UV filters with oil, surfactant, and water are bringing down the SPF values <20 38‐41 . As per the FDA recommendations, sunscreen products with SPF values <10, <25, <40, and >50 are considered as low, medium, high and very high protection respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sunscreen formulated with the combination of conventional UV filter agents and special organic ingredients like octinoxate, octisalate, oxybenzone, homosalate, avobenzone, octocrylene has shown better SPF values 40,42 . While the combination of these UV filters with oil, surfactant, and water are bringing down the SPF values <20 38‐41 . As per the FDA recommendations, sunscreen products with SPF values <10, <25, <40, and >50 are considered as low, medium, high and very high protection respectively.…”
Section: Discussionmentioning
confidence: 99%
“…40,42 While the combination of these UV filters with oil, surfactant, and water are bringing down the SPF values <20. [38][39][40][41] As per the FDA recommendations, sunscreen products with SPF values <10, <25, <40, and >50 are considered as low, medium, high and very high protection respectively. Meanwhile, the sunscreen manufacturers recommend that, any materials with an SPF of 15 is capable of blocking 90% UV radiation and are ideal for making sunscreens.…”
Section: Discussionmentioning
confidence: 99%
“…Clam shell powder has a potential as a new biomaterial with high calcium, phosphate, chitin and protein that gives a great result in preventing UV light [99]. Hydroxyapatite from shells can thus be used as an additive in the formulation of emulsions of sunscreen lotions, by the substitution of oxybenzone, zinc oxide and titanium dioxide [3,99,100]. In particular, avobenzone and oxybenzone act as an absorber of UVA and UVB, while titanium dioxide and zinc oxide act as physical blockers of UV radiation in sunscreen formulation.…”
Section: Cosmeticsmentioning
confidence: 99%
“…In recent years, HA has been proposed as a safe sunscreen ingredient, and the interest in CaPs for this application is growing [195,196]. In the literature, there are several examples that report the preparation of HA as a safe inorganic sunscreen ingredient to replace ZnO and TiO 2 [197][198][199][200][201][202][203][204][205][206][207][208][209][210][211]. Indeed, it was found that HA shows not only non-toxicity and biocompatibility properties, but also screening capability, high dermal tolerance, and a lower whitening effect than other inorganic sunscreen agents.…”
Section: Skin Protection-sunscreen (Uv Protection)mentioning
confidence: 99%
“…This material could be used for wound dressing, because it reduces bacterial infection while protecting wounds from UV exposure [205]. Another example is the work of Ghazali et al, which reports the preparation of an active sunscreen ingredient from clamshells by substituting calcium ions of HA structure with Fe 3+ or Mn 2+ [210]. The authors characterized the materials through X-ray diffraction, infra-red spectroscopy, and UV-visible spectrometry, and they determined the capability of samples to absorb UV light.…”
Section: Natural Calcium Phosphates As Sunscreensmentioning
confidence: 99%